Adverse Outcome Pathways (AOPs) development, a tool for predictive nanotoxicology - Rolo, Dora (2020)
Nanomaterials (NMs) have the potential to improve novel and useful wide applications in electronics, chemicals, environmental protection, biological medicine, food and others. Therefore, NMs rapid proliferation presents a dilemma to regulators regarding hazard identification, with increased concerns for public health. Predictive nanotoxicology describes a multidisciplinary approach to NMs evaluation that uses a set of in vitro and in silico methods to forecast the effects on biological systems. This approach offers advantages to traditional hazard assessment methods, such as reducing the reliance on animal studies, associated costs and ethical issues. It may be used with several applications in environmental and human health risk assessment and NMs hazard identification, as well as for regulation. The Adverse Outcome Pathways (AOPs) are the central element of a toxicological knowledge framework, promoted by member countries through OECD, built to support chemical risk assessment based on mechanistic reasoning. AOPs describes a logical sequence of causally linked events at different levels of biological organisation, which follows exposure and leads to an adverse health effect in humans or wildlife. The integrative analysis of the cellular and molecular mechanisms of nanotoxicity towards a definition of key events, may lead to adverse outcomes, driving a sequential line and defining an AOP landscape. Each defined AOP is available for crossing data, linking known and unknown landscapes. Since the biological effects that relate to possible genotoxicity and increased risk of cancer due to NMs exposure are under analysis, the development and assessment of AOPs are important novel strategic tools for predictive nanotoxicology.